Study of mosaicism of Pyropia yezoensis. Issue 2 (7th February 2019) - He, Yuan; Zhou, Wei; Li, Jiaming; Shen, Songdong
ABSTRACT: Cytological observations and sequence analysis of the ribosomal intergenic spacer (IGS) were conducted on conchospores and thalli of Pyropia yezoensis from China. The complete progress of conchospore germination of P. yezoensis was observed, and a tracking study of P. yezoensis mosaics was conducted by microscope, our results showed that the thallus is haploid, with three chromosomes; and the conchocelis is diploid, with six chromosomes. Conchospore germination of P. yezoensis developed in a linear pattern, and cell divisions were not synchronous. The thallus of P. yezoensis was divided into ten parts in our study, IGS was used as a molecular marker to conduct a sequence analysis of different portions of a complete thallus (the reproductive region, nutrient region, and base). P. yezoensis is mosaic of different genetic material based on molecular level differences among the IGS sequences of the different parts of P. yezoensis . The thallus was homozygous; with either two or three mosaics. Chimerism of Pyropia was proven at both the morphological and the molecular level. The results of our study supported the dominant view that meiosis of Pyropia occurs during conchospore germination.